A biomarker and therapeutical target in immune thrombocytopenia: TNF receptor-associated factor 6. (17th December 2018) - Asoglu, Veysi; Umit, Elif G; Demir, Muzaffer
Background: Immune thrombocytopenia (ITP) is an acquired disease characterized by various pathogenetic mechanisms. We aimed to evaluate the value of TRAF6 as a biomarker of pathogenesis in ITP.Methods:  85 newly diagnosed ITP patients and 85 controls were included.Results: In the patient group, mean TRAF6 level was 2348 pg/ml and in the control group, TRAF6 level was 25.57 pg/ml. In corticosteroid-responding patients, TRAF6 levels were lower than nonresponding patients.Discussion: TRAF6 levels were observed to be higher than healthy controls, which suggest a solid relation with ITP pathogenesis. The observation that in patients who present with high TRAF6 levels, there was a significant corticosteroid refractoriness and responsiveness.